PENGARUH PEMANASAN PNF (Propioceptive Neuromuscular Facilitation) TERHADAP TEKNIK DASAR TENDANGAN DOLLYO CHAGI PADA SISWA EKSTRAKURIKULER DI SMPN 59 JAKARTA - Fajriansyah Surba, Arzaki; Susianti, Evi; Bayu Mahardika, Dhika (Jurnal Porkes, 2024)
The problem contained in this study is the lack of maximum students in doing dollyo chagi kicks, student kicking power in performing basic dollyo chagi kick techniques in extracurricular Taekwondo. The purpose of this study was to examine the PNF warm-up method affects the results of dollyo chagio kicks in Taekwondo extracurricular students at SMPN 59 Jakarta. This research uses descriptive quantitative using experimental methods. The population used in this study were 25 Taekwondo extracurricular students. The research design used a one group pretest-postest design. The instrument in this study used pretest and postest. The data analysis used is descriptive statistics displayed in percentage form. The research results show that the t value is 18.384 > t table 1.711 and a significant value of 0.000 < 0.05, meaning that Ho is rejected and Ha is accepted or it can be said that the PNF warm-up method really has a significant effect on the results of dollyo chagi kicks for taekwondo extracurricular students of SMPN 59 Jakarta.